Implementation of Digital Media in Improving Higher Order Thinking Skills (Hots) in IPAS Subjects - Siti Anisatun Nafi'ah; Wahyu Hidayat; Rizki Agung Wijayati Hadi Safitri; Vidya Pandan Wangi (Doctoral Program In Elementary Madrasah Teacher Education Faculty Of Tarbiyah And Education - UIN Sunan Kalijaga Yogyakarta, 2026)
Abstract The purpose of this study is to improve students' understanding in HOTS-based science learning on the material